Pengaruh Desinfeksi Energi Microwave Terhadap Kekuatan Transversal Resin Akrilik Polimerisasi Panas - Sefty Aryani Harahap; Lasminda Syafiar; Yosepha Yulinda Esdaria Lubis (Jurnal Material Kedokteran Gigi, 2019)
Disinfectant by microwave energy is highly recommended as a solution to solve the problem of chemical disinfection on denture bases. One of the denture base materials is heat cured acrylic resin. Aim, to evaluate the effect of disinfectant by microwave energy with different time on the transversal strength of heat cured acrylic resin. 30 plates (n = 6) of heat cured acrylic resin with size 65x10x2,5 mm were divided into 5 groups (control; and microwave energy disinfected for 2, 4 , 6, and 8 minutes with 650 Watts of power). Transversal strength test was carried out using Torsee's Electronic System Universal Testing Machine with a test speed of 0.1 mm / second, and a load cell of 50 kgf. Data analyzed using one-way ANOVA and LSD pos hoc. Results, there were significant differences in the transverse strength among all groups (p <0.05). Mean values of all groups were 103.59 ± 0.66 MPa; 112.02 ± 2.10 MPa; 117.48 ± 1.73 MPa; 125.46 ± 2.25 MPa; and 135.89 ± 1.56 MPa respectively. Conclusion, the longer it is disinfected by microwave energy, the higher the transversal strength of heat cured acrylic resin.